Improving English Proficiency Skills Through Literary Works - Sari, Dhea Trisna; subari, Susiati (Journal of English Language and Education, 2025)
This study explores learning through literary works contribute on the English proficiency and learning improvement of students at Universitas Muhammadiyah Surakarta (UMS). Literature, including novels, short stories, poetry, and drama, serves as an effective medium for enhancing students’ vocabulary, grammar comprehension, and overall language skills. Using a qualitative research approach, the study examines students’ experiences in engaging with literary texts and analyzes how these engagements contribute to their motivation and linguistic development. The findings indicate that reading literary works significantly enriches students’ vocabulary, strengthens their understanding of grammar, and improves their speaking, listening, reading, and writing skills. Additionally, literary engagement fosters critical thinking and cultural awareness, making language learning more immersive and enjoyable. The research also highlights the benefits of integrating literature with other learning methods to create a more holistic approach to language acquisition. In conclusion, the study emphasizes the importance of incorporating literary works into English language curricula to enhance students’ proficiency and academic growth.